Эффективность приема по нуль-переходам элементов сигнальных конструкций на выходе бинарного канала - Захарченко, Николай Васильевич; Гаджиев, М. М.; Шинкарчук, Т. Н. (Eastern-European Journal of Enterprise Technologies, 2009)
Is Theoretically proved and experimental is confirmed big noise-immunity temporary parameter zero-transition in contrast with other information parameter